Taking Anamnesis and Examination of the Articulatory Apparatus with Erased Dysarthria - S. J, Achilova (International Journal on Orange Technologies, 2022)
This article examines the articulatory speech apparatus in children with dysarthria and the collection of anamnestic data. Information on their analysis is also provided.